Meeting report: 36th International Conference on Antiviral Research in Lyon, France - March 13-17, 2023 - Spengler, Jessica R; Carter, Kara; Delang, Leen; Durantel, David; Gowen, Brian B; Herrero, Lara J; Hurst, Brett; Janeba, Zlatko; Jordan, Robert; Luo, Dahai; Meier, Chris; Moffat, Jennifer; et al. (Antiviral research, 2023)
The 36th International Conference on Antiviral Research (ICAR), sponsored by the International Society for Antiviral Research (ISAR), was held March 13-17, 2023, in Lyon, France, and concurrently through an interactive remote meeting platform. Here we provide a report summarizing the presentations at the 36th ICAR, including the ISAR speaker awards. We also detail special events, sessions, and additional awards conferred at the meeting. ICAR returned to in-person meetings in 2022, convening in Seattle, WA, USA. The 36th ICAR is the first in-person meeting of the society in Europe since the beginning of the COVID-19 pandemic, which restricted most events to virtual attendance to help mitigate the spread and subsequent public health impact of SARS-CoV-2. An exceptionally high number of registrants and record attendance at this year's ICAR, along with a vast array of demonstrable expertise in a variety of antiviral research-related fields, reflected a strong and growing antiviral research community committed to improving health outcomes from viral diseases, including SARS-CoV-2, and to future pandemic preparedness. This report highlights the breadth of expertise, quality of research, and notable advancements that were contributed by members of ISAR and other participants at the meeting. ICAR aims to continue to provide a platform for sharing information, fostering collaborations, and supporting trainees in the field of antiviral research. The 37th ICAR will be held in Gold Coast, Australia, May 20-24, 2024.
Keywords: pandemie; železo-dextranový komplex; Antiviral Agents; Iron-Dextran Complex; lidé; SARS-CoV-2; Pandemics; antivirové látky; COVID-19; Humans